RAPPORTI FRA I PRODOTTI RESIDUALI DEL CARSISMO E LA SEDIMENTAZIONE QUATERNARIA NELL'AREA DELLE MURGE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
The presence of red clays and silts, alternated with micritic limestones in the lower part of the Calcarenite di Gravina Formation (Lower Pleistocene) proves that, in some zones of the Murge area, the sedimentation was affected by residual materials coming from dissolution of Cretaceous limestones. The stratigraphyc data concerning the whole formation indicate that these environmental conditions took piace at the beginning of the pliopleistocenic transgression only; i, e. until the residual materials, produced and amassed by karst on the Murge area, reached the basin. The presedimentary morphotectonic setting was also of gecat importance: the presence of some hollows, prehexisting to the transgression, favoured the accumulation and the preservation of murgian terrigenous materials, which in other areas were removed by the sea action.
Keywords: Karst; Quaternary sedimentation; South ltaly.